2014
DOI: 10.1136/tobaccocontrol-2013-051451
|View full text |Cite
|
Sign up to set email alerts
|

Equity impact of interventions and policies to reduce smoking in youth: systematic review

Abstract: Very few studies have assessed the equity impact of tobacco control interventions/policies on young people. Price/tax increases had the most consistent positive equity impact. There is a need to strengthen the evidence base for the equity impact of youth tobacco control interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 52 publications
(150 reference statements)
5
87
0
Order By: Relevance
“…The imperative to address the unequal distribution of smoking comes after decades of research showing the potentially unequal influence of tobacco control initiatives on smoking behaviour. 21 This issue remains critically important in light of the deficient evidence on interventions able to reliably reduce smoking-related inequalities 22,23 and the widening of inequalities in smoking initiation over time. [24][25][26] Consistent with an increasing amount of research on young adult initiation, [10][11][12][13] we found that proportions of initiation made during young adulthood had not decreased in our retrospective cohorts between 2001 and 2013.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The imperative to address the unequal distribution of smoking comes after decades of research showing the potentially unequal influence of tobacco control initiatives on smoking behaviour. 21 This issue remains critically important in light of the deficient evidence on interventions able to reliably reduce smoking-related inequalities 22,23 and the widening of inequalities in smoking initiation over time. [24][25][26] Consistent with an increasing amount of research on young adult initiation, [10][11][12][13] we found that proportions of initiation made during young adulthood had not decreased in our retrospective cohorts between 2001 and 2013.…”
Section: Discussionmentioning
confidence: 99%
“…These include school-based and community interventions, anti-smoking media campaigns, tobacco advertising restrictions, and youth access restrictions. 2,3 Certain public health institutions, including the Surgeon General's Office 4 and the Institute of Medicine, 5 have proposed to extend this age bracket up to 25 years of age and establish new priorities specific to the young adult (18)(19)(20)(21)(22)(23)(24)(25) age group. In Canada, cigarette smoking prevalence is now highest among young adults.…”
mentioning
confidence: 99%
“…4 Adolescents from lower socioeconomic status (SES) backgrounds are more price-sensitive to such increases than those from higher SES backgrounds. 6 In Australia, increased cigarette prices have been strongly associated with reductions in smoking across the general population, lower SES quintiles and adolescents. 7,8 Between 1990 and 2005, the average price of a cigarette rose from $0.18 to $0.41.…”
Section: Price and Tax Measures To Reduce Demand For Tobaccomentioning
confidence: 99%
“…This broad range of smoking-related outcomes was included in order to encompass the diverse ways in which tobacco control policies can influence youth smoking-related outcomes.' (Brown, Platt, and Amos 2014a) • 'Changes in equity of access -increased access for disadvantaged groups or a reduction in gaps in coverage -could also be an important outcome measure. This required a preliminary analysis and categorisation of the population of interest along a socio-economic scale.…”
Section: Methods Sectionmentioning
confidence: 99%